The α(1)β(1) and α(2)β(1) Integrins Provide Critical Support for Vascular Endothelial Growth Factor Signaling, Endothelial Cell Migration, and Tumor Angiogenesis - Senger, Donald R. (American Society for Investigative Pathology, 2002)
Angiogenesis is a complex process, involving functional cooperativity between cytokines and endothelial cell (EC) surface integrins. In this study, we investigated the mechanisms through which the α(1)β(1) and α(2)β(1) integrins support angiogenesis driven by vascular endothelial growth factor (VEGF). Dermal microvascular EC attachment through either α(1)β(1) or α(2)β(1) supported robust VEGF activation of the Erk1/Erk2 (p44/42) mitogen-activated protein kinase signal transduction pathway that drives EC proliferation. Haptotactic EC migration toward collagen I was dependent on α(1)β(1) and α(2)β(1) as was VEGF-stimulated chemotaxis of ECs in a uniform collagen matrix. Consistent with the functions of α(1)β(1) and α(2)β(1) in supporting signal transduction and EC migration, antibody antagonism of either integrin resulted in potent inhibition of VEGF-driven angiogenesis in mouse skin. Moreover, combined antagonism of α(1)β(1) and α(2)β(1) substantially reduced tumor growth and angiogenesis of human squamous cell carcinoma xenografts. Collectively, these studies identify critical collaborative functions for the α(1)β(1) and α(2)β(1) integrins in supporting VEGF signal transduction, EC migration, and tumor angiogenesis.